The structure and assembly of rhizobacterial communities are influenced by poplar genotype - Zhu, Qi Liang; Yan, Kun; Wang, Nian Zhao; Ma, Shu Qi; Lu, De Shan; Su, Xiao Hua; Yuan, Zheng Sai; Dong, Yu Feng; Wang, Yan Ping; Ding, Chang Jun (Frontiers in Microbiology, 2022)
The interaction between plants and microbes dominates plant growth and fitness in specific environments. The study of the relationship between plant genotypes and rhizobacterial community structure would provide a deep insight into the recruitment strategies of plants towards soil bacteria. In this study, three genotypes of 18-year-old mature poplar (H1, H2, and H3) derived from four different parents were selected from a germplasm nursery of Populus deltoides. Rhizosphere soil carbon, nitrogen, and phosphorus properties as well as the 16S rDNA sequences of rhizobacterial communities were analyzed to determine the relationship between poplar genotypes and rhizobacterial communities assembly. The results showed there were significant differences in the diversity (Chao1, ACE index, and Shannon index) of rhizobacterial communities between H1 and H2, as well as between H2 and H3, but no difference between H1 and H3. Principal component analysis also revealed a similar structure of rhizobacterial communities between H1 and H3, whereas the rhizobacterial communities of H2 demonstrated significant differences from H1 and H3. Linear discriminant effect size analysis indicated that there were 11 and 14 different biomarkers in the H1 and H3 genotype, respectively, but 42 in the H2 genotype. Co-occurrence network analysis indicated that the rhizobacterial communities of H2 had a distinct network structure compared to those of the other two genotypes, whereas H1 and H3 had a similar pattern of co-occurrence network. Threshold indicator taxa analysis revealed that 63 genera responded significantly to NO3–N content and 58 genera to NH4+-N/NO3–N ratio. Moreover, the stochastic assembly process was found to be decreased with increasing NO3–N content and fluctuated with increasing NH4+-N/NO3–N ratio. All results indicated that the structure of poplar rhizobacterial communities were influenced by host genotypes, and available nitrogen might play a dominant role in the assembly of rhizobacterial communities. This study would promote the future selection and utilization of rhizobacteria in poplar breeding.